Concept as a means of representation of ethno cultural mentality - Derbisheva Замира; Altynbekova Гульжан (Turkic Studies Journal, 2021)
This article is devoted to a problem of studying an emotional concept «Mahabbat / Love» in the Kazakh and Kyrgyz languages. A person’s knowledge of the world starts developing from the moment of his birth. It consists of concepts that are different according to the level of complexity and abstraction. Concepts are basis for understanding national mentality. A concept «Mahabbat / Love» that reflects emotional behavior of an ethnic community, refers to numerous images in Kazakh and Kyrgyz consciousness and represented in lexicon, phraseological units, proverbs and sayings, poetic texts. For comprehensive representation of this concept authors consider natural use of lingua-cultural, axiological, lingua-cognitive, semantic-pragmatical approaches.